Fundamental study of detection of muscle hypertrophy-oriented gene doping by myostatin knock down using RNA interference - Takemasa, T.; Yakushiji, N.; Kikuchi, D. M.; Deocaris, C.; Widodo; Machida, M.; Kiyosawa, H. (Journal of Sports Science & Medicine, 2012)
To investigate the feasibility of developing a method for detection of gene doping in power-athletes, we devised an experimental model system. Myostatin is a potent negative regulator of skeletal muscle development and growth, and myostatin-knockout mice exhibit a double-muscle phenotype. To achieve knockdown, we constructed plasmids expressing short hairpin interfering RNAs (shRNAs) against myostatin. These shRNAs were transfected into C2C12 cultured cells or injected into the tibialis anterior (TA) muscle of adult mice. By performing in vitro and in vivo experiments, we found that some shRNAs effectively reduced the expression of myostatin, and that the TA muscle showed hypertrophy of up to 27.9%. Then, using real-time PCR, we tried to detect the shRNA plasmid in the serum or muscles of mice into which it had been injected. Although we were unable to detect the plasmid in serum samples, it was detectable in the treated muscle at least four weeks after induction. We were also able to detect the plasmid in muscle in the vicinity of the TA. This gene doping model system will be useful for further studies aimed at doping control.